2011
DOI: 10.1111/j.1741-2358.2011.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral health and body cell mass in hospitalised elderly

Abstract: Association between oral health and body cell mass in hospitalised elderlyObjective: To examine whether oral health in hospitalised elderly was associated with body cell mass (BCM) measured with Bioimpedance spectroscopy. Background: Body cell mass is the tissue producing the metabolic work necessary for all body functions. BCM is mainly muscle tissue. Low BCM is associated with diseases, ageing and poor nutritional status. Reduced oral health is also associated with these parameters; thus, BCM and oral health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Body cell mass differs from body mass index in that body mass index includes body fluids as well as muscle mass; body cell mass includes only muscle mass. A significant association between poor oral health status/reduced oral hygiene and low body cell mass was observed, and the results remained significant after adjusting for confounders such as age, gender, smoking, education level and number of medications . The findings were important for demonstrating that there was a lower number of remaining teeth in patients with reduced body cell mass.…”
Section: Oral Health Status Aging and Loss Of Teethmentioning
confidence: 78%
“…Body cell mass differs from body mass index in that body mass index includes body fluids as well as muscle mass; body cell mass includes only muscle mass. A significant association between poor oral health status/reduced oral hygiene and low body cell mass was observed, and the results remained significant after adjusting for confounders such as age, gender, smoking, education level and number of medications . The findings were important for demonstrating that there was a lower number of remaining teeth in patients with reduced body cell mass.…”
Section: Oral Health Status Aging and Loss Of Teethmentioning
confidence: 78%
“… 18 Moreover, oral hygiene has usually deteriorated in the sarcopenia group, and the risk of infection is higher when oropharyngeal material has been aspirated. 19 Juthani-Mehta et al 20 showed that the body composition and oral hygiene are important factors in pneumonia. In the present study, the authors have also shown that the decrease in BMI resulted in pneumonia, which would indicate hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Low BCM was found to be associated with poor nutrition, low muscle strength, and reduced functional performance 27. A positive relationship has been shown to occur between BCM and HGS,26,28 and a negative correlation has been detected between the BCM and the number of medications 26. Lauretani et al found correlations between HGS and the parameters determined by measurements of electric bioimpedance adjusted for body height 29…”
Section: Discussionmentioning
confidence: 99%